2009
DOI: 10.1111/j.1468-1293.2009.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department utilization among HIV‐infected patients in a multisite multistate study*

Abstract: Objective-The aim of this study was to examine Emergency Department (ED) utilization and clinical and sociodemographic correlates of ED use among HIV-infected patients.Methods-During 2003, 951 patients participated in face-to-face interviews at 14 HIV clinics in the HIV Research Network. Respondents reported the number of ED visits in the preceding 6 months. Using logistic regression, we identified factors associated with visiting the ED in the last 6 months and admission to the hospital from the ED.Results-Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
6
25
0
Order By: Relevance
“…56 ED use correlates with high primary care clinic use, current or former illicit drug use, Medicaid enrollment, and female gender, but not with any biologic markers of HIV severity. 56 If this pattern of frequent healthcare utilization is not driven by health issues themselves, there are likely other contributing factors external to the actual ED visit. Given the impact of violence on mental health, substance abuse, and risk taking already discussed, this health-seeking behavior may, in part, also be influenced by experiences of violence.…”
Section: Effect Of Sava On Healthcare Utilization and Combination Antmentioning
confidence: 99%
“…56 ED use correlates with high primary care clinic use, current or former illicit drug use, Medicaid enrollment, and female gender, but not with any biologic markers of HIV severity. 56 If this pattern of frequent healthcare utilization is not driven by health issues themselves, there are likely other contributing factors external to the actual ED visit. Given the impact of violence on mental health, substance abuse, and risk taking already discussed, this health-seeking behavior may, in part, also be influenced by experiences of violence.…”
Section: Effect Of Sava On Healthcare Utilization and Combination Antmentioning
confidence: 99%
“…Yet, in contrast to studies examining inpatient and out patient health care use, [2][3][4][5][6] comparatively few contemporary studies exist examining emergency department use among people with HIV. [7][8][9][10][11] Studies conducted in the years pre ceding the introduction of combination antiretroviral ther apy demonstrated that people with HIV had rates of emer gency department visits that were three to fourfold higher than those of the general population. 12,13 Although subse quent studies found persistently heightened rates of emer gency department use following the introduction of com bination antiretroviral therapy, inferences were limited by samples that were small and not populationbased.…”
mentioning
confidence: 99%
“…12,13 Although subse quent studies found persistently heightened rates of emer gency department use following the introduction of com bination antiretroviral therapy, inferences were limited by samples that were small and not populationbased. 7,9,10 A recent analysis of the US National Hospital Ambulatory Medical Survey demonstrated that rates of emergency department visits among people with HIV continue to exceed those of noninfected people (633 v. 438 visits per 1000 people), although by a smaller magnitude than during the preceding decade. 14 Analogous populationbased studies characterizing emer gency department use among people with HIV in a Canadian setting are lacking.…”
mentioning
confidence: 99%
“…Nowadays, as discussed above, HIV patients come to the ED more often due to pathologies that are not directly associated with HIV. This will continue to be the trend in patients with good immunological control, which, in turn, will entail longer hospital stays and higher utilization of health resources, 10,11,33 with the aim of reducing their morbimortality and related healthcare costs. 34 Finally, our study shows a decrease in the incidence of LRTI and associated mortality, even though it has not remained significant (14%) in the last ten years.…”
Section: Discussionmentioning
confidence: 99%
“…The changing situation of HIV patients in the HAART era has led to changes in the reasons to seek emergency care along the years. 11 However, these changes may not be well understood. We have been prospectively collecting data on ED admissions at Hospital Clinic, a major hospital located in the center of Barcelona delivering emergency care for a wide urban area.…”
Section: Introductionmentioning
confidence: 99%